ON COMPETITION OF LANGUAGES IN THE REPUBLIC OF UZBEKISTAN - Ayjan Azizbekqizi Anarbekova (Journal Park Publishing, 2023)
Achieving independence, giving the Uzbek language the status of the state language, allowed the Uzbek language in the conditions of national statehood to acquire the rank of the state official language, knowledge of which is the responsibility of every citizen of the Republic of Uzbekistan.
Keywords: language-teaching, methodology of teaching English, pedagogy, teaching methods, verbs.